2022
DOI: 10.1016/j.nmd.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic eosinophilic myositis: a systematic literature review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…They are critical effectors of the type 2 inflammatory response with a long-standing association with multiple diseases including allergic rhinitis, asthma eosinophilic, chronic rhinosinusitis, and esophagitis [ 49 , 52 ]. Muscle eosinophilia has been reported in several neuromuscular diseases including Duchenne and Becker Muscular Dystrophy [ 53–56 ], LAMA2 -CMD muscular dystrophy [ 57 ], Limb-girdle muscular dystrophy [ 58 , 59 ], and idiopathic eosinophilic myositis [ 60 , 61 ]. However, the only study to date that quantified eosinophils in FSHD reported an increase in the hemogram eosinophil count in 1 out of 3 FSHD patients analyzed [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are critical effectors of the type 2 inflammatory response with a long-standing association with multiple diseases including allergic rhinitis, asthma eosinophilic, chronic rhinosinusitis, and esophagitis [ 49 , 52 ]. Muscle eosinophilia has been reported in several neuromuscular diseases including Duchenne and Becker Muscular Dystrophy [ 53–56 ], LAMA2 -CMD muscular dystrophy [ 57 ], Limb-girdle muscular dystrophy [ 58 , 59 ], and idiopathic eosinophilic myositis [ 60 , 61 ]. However, the only study to date that quantified eosinophils in FSHD reported an increase in the hemogram eosinophil count in 1 out of 3 FSHD patients analyzed [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an exhaustive literature review about IEM, 69 published cases of IEM were analysed [ 3 ]. These cases were classified according to the previously mentioned classification [ 2 , 10 , 12 ], based only on the histological pattern, which included focal IEM, diffuse IEM (initially referred to as eosinophilic polymyositis) and eosinophilic perimyositis.…”
Section: Discussionmentioning
confidence: 99%
“…The findings concerning immunostaining (MHC-I, CD56, CD3, CD4, CD8, CD20, CD68, CD138) include a number of missing data, due to technical considerations and sample availability, and thus need to be further confirmed. Nevertheless, with only 69 cases published in the literature so far [ 3 ], this study represents the largest IEM/EF case series. The review of muscle biopsies by three clinicians allowed to decrease potential interpretation biases while the complete review of patient records was performed by a single clinician in order to standardize data collection.…”
Section: Discussionmentioning
confidence: 99%